2005
DOI: 10.1038/sj.bjc.6602527
|View full text |Cite
|
Sign up to set email alerts
|

A potent nonporphyrin class of photodynamic therapeutic agent: cellular localisation, cytotoxic potential and influence of hypoxia

Abstract: We have developed a totally new class of nonporphyrin photodynamic therapeutic agents with a specific focus on two lead candidates azadipyrromethene (ADPM)01 and ADPM06. Confocal laser scanning microscopy imaging showed that these compounds are exclusively localised to the cytosolic compartment, with specific accumulation in the endoplasmic reticulum and to a lesser extent in the mitochondria. Light-induced toxicity assays, carried out over a broad range of human tumour cell lines, displayed EC 50 values in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(62 citation statements)
references
References 22 publications
4
58
0
Order By: Relevance
“…It is possible that the mono-styryl-diiodo-BODIPYs bind preferentially to anti-apoptotic Bcl-2 proteins compared with their di-styryl analogs, causing cell apoptosis and/or autophagy [53], leading to rapid cell death. Previous studies have also shown that phototoxic BODIPYs tend to localize preferentially in the ER or mitochondria [2429]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that the mono-styryl-diiodo-BODIPYs bind preferentially to anti-apoptotic Bcl-2 proteins compared with their di-styryl analogs, causing cell apoptosis and/or autophagy [53], leading to rapid cell death. Previous studies have also shown that phototoxic BODIPYs tend to localize preferentially in the ER or mitochondria [2429]. …”
Section: Resultsmentioning
confidence: 99%
“…Their remarkable photophysical properties, including high extinction coefficients, easily tunable absorption and emission profiles, high stability and solubility, as well as their known ability to permeate cells, make them suitable for exploration as PDT agents [21,22]. It has been shown that some BODIPYs bearing heavy atoms, such as iodine or bromine, display cytotoxic properties when exposed to light while others remain non-toxic [2329]. The effects of the “spin-orbit couplings” of heavy atoms favor intersystem crossing from the excited singlet to the triplet state needed for singlet oxygen generation [3032].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies have shown the ADPM family of photosensitisers to be an exciting new class of agents having significant potential for preclinical development (Gorman et al, 2004;Gallagher et al, 2005). Unlike many other PDT photosensitisers, ADPM agents are synthetic and can be readily modified about the core periphery to affect drug properties (McDonnell et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported the discovery of a novel class of non-porphyrin-based modifiable PDT agents, termed the BF 2 -chelated tetraaryl-azadipyrromethenes (ADPMs), and have shown in vitro that their photophysical and biological characteristics have significant potential for the development as new anti-cancer therapeutics (Gorman et al, 2004;Gallagher et al, 2005). We have shown that this new class of PDT agent possesses excellent photophysical properties and as having EC 50 values in the low nano-molar range for lead compound ADPM06, with no discernable activity bias for a specific tumour cell type.…”
mentioning
confidence: 99%
“…Further development of the aza-BODIPYs as effective anticancer therapeutics required comprehensive studies on ADPM06. 132 The lead compound displayed localization in the cytoplasmic compartment with a large accumulation in the endoplasmic reticulum with minor localization to the mitochondria. ADPM06 induced apoptosis as a mechanism for cell death.…”
Section: E32 Aza-bodipy Photosensitizersmentioning
confidence: 99%